2010
DOI: 10.1007/s11199-010-9803-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Mother-toddler and Father-toddler Verbal Initiations and Responses during a Caregiving and Play Context

Abstract: Contextual variations in mother-child and fatherchild verbal communication were examined among 80 U.S. families from Kansas who were predominately Caucasian (85%) and middle-class. There were 41 girls and 39 boys between 15-and 18-months-old observed with their mothers and fathers in separate play and caregiving laboratory situations. Parent and child behaviors were coded for verbal initiation and response strategies. MAN-OVA's revealed more differences between mother's and father's verbal communication strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Parents, who are socialized with gender schemas, transfer the knowledge to their daughters and sons through different verbal responses. Fathers, on the contrary, generally have more physical play with their children (e.g., Lindsey et al, 2010). Interestingly, Clearfield and Nelson (2006) reported that the different communication styles toward daughters and sons occurred as early as 6 months of age, when the infants were not able to speak yet.…”
Section: Family Factorsmentioning
confidence: 99%
“…Parents, who are socialized with gender schemas, transfer the knowledge to their daughters and sons through different verbal responses. Fathers, on the contrary, generally have more physical play with their children (e.g., Lindsey et al, 2010). Interestingly, Clearfield and Nelson (2006) reported that the different communication styles toward daughters and sons occurred as early as 6 months of age, when the infants were not able to speak yet.…”
Section: Family Factorsmentioning
confidence: 99%
“…A large literature has shown that positive maternal disciplinary strategies are negatively related to children's empathetic and prosocial tendencies and that parental inductions predict sociomoral competence (e.g., deVeer & Janssens, 1994; Hoffman & Saltzstein, 1967;Miller et al, 1989). However, most of these studies included only mothers, despite evidence that women and men have unique parenting roles and that their parenting styles are sometimes differentially related to child outcomes (Cassano, Adrian, Veits, & Zeman, 2006;Lindsey, Cremeens, & Caldera, 2010). The current findings point to a need for more research that considers mothers and fathers as part of an interdependent family system.…”
Section: Discussionmentioning
confidence: 88%
“…Other research has found that parents give toddler girls more assistance in physical tasks than toddler boys, regardless of their abilities (Morrongiello & Dawber, 1999) and are more likely to initiate pretend play with pre-school girls than boys (Lindsey et al, 1997). Fathers also tend to be more involved in their son's lives (Raley & Bianchi, 2006) and ignore their daughter's play initiations (Lindsey, Cremeens, & Caldera, 2010) while girls have more involvement from parents than boys (Carter & Wojtkiewicz, 2000) but are controlled by parents more (Smetana & Daddis, 2002;Van Lissa et al, 2019). The inequality in how we treat our sons and daughters' merits continued investigations.…”
Section: Conc Lusionsmentioning
confidence: 99%